Antibodies and Acidic Environment Do Not Enhance HIV-1 Transcytosis. (4th August 2016) - Gonzalez, Oscar A.; Sagar, Manish
Abstract: A limited number of human immunodeficiency virus type 1 (HIV-1) variants initially infect HIV-1–naive individuals. Recent studies imply that this may occur because generally inefficient transcytosis across intact mucosal surfaces could be enhanced for specific viruses with bound antibodies and in the presence of acidic pH. We found that transcytosis of both cell-free and cell-associated viruses with diverse envelopes was significantly decreased in the presence of either antibodies or plasma from chronically infected transmitting partners regardless of pH. Transmitted variants also did not have greater transmigration as compared to chronic-infection strains. Enhanced translocation capacity is unlikely to influence which HIV-1 variant establishes infection.